Native and non-native (L1-Mandarin) speakers of English differ in online use of verb-based cues about sentence structure - QIAN, ZHIYING; LEE, EUN-KYUNG; LU, DORA HSIN-YI; GARNSEY, SUSAN M. (Bilingualism (Cambridge, England), 2019)
This study examined whether L1-Mandarin learners of L2-English use verb bias and complementizer cues to process temporarily ambiguous English sentences the same way native speakers do. SVO word order places verbs early in sentences in both languages, allowing the use of verb-based knowledge to anticipate what could follow. The two languages differ, however, in whether an optional complementizer signals embedded clauses. In a self-paced reading experiment, native English speakers and L1-Mandarin learners of L2-English read sentences containing temporary ambiguity about whether a noun was the direct object of the verb preceding it or the subject of an embedded clause. Native speakers replicated previous work showing an optimally efficient interactive pattern of cue use, while non-native learners showed additive effects of the two cues, consistent with predictions of the Competition Model about learning how to use multiple cues in a second language that sometimes agree and sometimes do not.